Makhana Cultivation in Bihar: A Rising Opportunity with the New Budget Announcement - Kumar, Sanjeev; Kumar, Rakesh; Mandal, Devendra (Indian Horticulture, 2025)
Makhana cultivation has become a significant contributor to Bihar's rural economy, especially in the Mithilanchal and Kosi regions, which together account for over 80% of India's makhana production. Renowned for its high protein, fiber, and mineral content, makhana has seen increasing demand both domestically and internationally due to its health benefits. In the Union Budget 2025–26,the Indian government announced the establishment of a dedicated Makhana Board in Bihar. This initiative aims to bolster the sector by supporting research, enhancing processing infrastructure, and expanding market access. Key measures include financial assistance for infrastructure development, promotion of exports, improvement of farmer welfare, and the adoption of sustainable practices.Emphasis on modernizing water management, improving seed quality, and fostering technological adoption is expected to further strengthen the industry. With robust government support, Bihar's makhana sector is poised for significant growth, offering farmers increased income opportunities and positioning the state as a global leader in the production of this nutritious superfood.